2012
DOI: 10.1111/aji.12038
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation Human Blastocyst‐Endometrial Interactions: The Role of Inflammatory Mediators

Abstract: Immune factors such as cytokines, chemokines, and growth factors are known to play important roles in the preimplantation interactions and communication between the blastocyst and receptive endometrium. This crucial dialog occurs during the stages when the blastocyst is in the uterine cavity immediately preceding implantation and the establishment of pregnancy. Human preimplantation processes are difficult to study due to restrictions on tissue availability. This review focuses on the expression and role of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 119 publications
1
26
0
2
Order By: Relevance
“…It is noteworthy that the downregulation of these two pro-inflammatory cytokines with all different progestin treatments is consistent with the known anti-inflammatory effects of progestins on human endometrium in vivo [11,16,39]. Early implantation is characterized by high levels of the pro-inflammatory T helper cells and cytokines such as TNFα, IL-6, and IL-8 [40,41], and the upregulation of pro-inflammatory cytokines positively correlates with IVF pregnancy outcomes [42]. Cytokines and chemokines such as IL-6 attract human trophoblast cells and therefore affect successful implantation [42], and the balance of pro-and anti-inflammatory cytokines and chemokines is required for proper endometrial tissue growth and remodeling [42,43].…”
Section: Chemokines Cytokines and Angiogenic Factorssupporting
confidence: 65%
“…It is noteworthy that the downregulation of these two pro-inflammatory cytokines with all different progestin treatments is consistent with the known anti-inflammatory effects of progestins on human endometrium in vivo [11,16,39]. Early implantation is characterized by high levels of the pro-inflammatory T helper cells and cytokines such as TNFα, IL-6, and IL-8 [40,41], and the upregulation of pro-inflammatory cytokines positively correlates with IVF pregnancy outcomes [42]. Cytokines and chemokines such as IL-6 attract human trophoblast cells and therefore affect successful implantation [42], and the balance of pro-and anti-inflammatory cytokines and chemokines is required for proper endometrial tissue growth and remodeling [42,43].…”
Section: Chemokines Cytokines and Angiogenic Factorssupporting
confidence: 65%
“…The impact of high RA disease activity on fertility could be mediated via inflammatory mediators, since many cytokines, chemokines and growth factors play an important role in the preimplantation blastocyst–endometrial interactions 22. We have previously shown that high IL-6 serum levels are associated with lower birth weight in children born to women with RA 23…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that pro‐inflammatory and anti‐inflammatory cytokines are intimately involved in blastocyst implantation, but their role in hatching phenomenon is less studied. The landscape of cytokine‐signalling pathways governing blastocyst hatching and how exactly a cohort of pro‐inflammatory and anti‐inflammatory cytokines communicates among themselves and with hatching‐enabling factors, thereby effectively promoting hatching remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%